2016
DOI: 10.1074/jbc.m116.719666
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the cAMP-PKA pathway Antagonizes Metformin Suppression of Hepatic Glucose Production

Abstract: Metformin is the most commonly prescribed oral anti-diabetic agent worldwide. Surprisingly, about 35% of diabetic patients either lack or have a delayed response to metformin treatment, and many patients become less responsive to metformin over time. It remains unknown how metformin resistance or insensitivity occurs. Recently, we found that therapeutic metformin concentrations suppressed glucose production in primary hepatocytes through AMPK; activation of the cAMP-PKA pathway negatively regulates AMPK activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…Western blot analysis was carried out as described earlier [19]. Briefly, cultured cells were harvested in cell lysis buffer (Cell Signaling Technology) and denatured in SDS loading buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis was carried out as described earlier [19]. Briefly, cultured cells were harvested in cell lysis buffer (Cell Signaling Technology) and denatured in SDS loading buffer.…”
Section: Methodsmentioning
confidence: 99%
“…20) Multiple additional phosphorylation sites in the α subunit have also been studied. 21) The α1Ser485 residue is involved in negative regulation of AMPK by cAMP-PKA. 22) In additional, phosphorylation of AMPKα Ser485/491, when stimulated with insulin, has been shown to lead to a decrease in AMPK activity.…”
Section: Multisite Phosphorylation Of Ampk Sub Unitsmentioning
confidence: 99%
“…37) Moreover, AMPKα Ser485/491, which was confirmed by using recombinant protein, 35) was also autophosphorylated to limit AMPK activation in response to energy depletion or other regulators. 21) The functional roles of additional AMPK autophosphorylation sites, such as α1Thr477, α1Ser349, β1Thr158, and β1Thr80, 38) requires further investigation.…”
Section: Multisite Phosphorylation Of Ampk Sub Unitsmentioning
confidence: 99%
“…Human and experimental animal studies showed that asprosin is significantly associated with glucose and insulin production in the liver during fasting, which means that the presence of asprosin could be a risk factor with regard to insulin resistance . Furthermore, decreasing the level of asprosin leads to the prevention of hyperinsulinemia, which is associated with metabolic syndrome It has been shown that increased asprosin levels in the liver trigger cyclic adenosine 3′, 5′‐monophosphate (cAMP) and protein kinase (PKA) signaling pathways, which has resulted in higher release of glucose from the liver into the circulation . In a recent animal study it was shown that aerobic exercise decreased the level of hepatic asprosin …”
mentioning
confidence: 99%